OLIVINA MELILITITO E FONOLITO: FONTES ALTERNATIVAS DE POTÁSSIO PARA A CULTURA DO MILHO CULTIVADO EM SOLO ARENOSO? - DIAS, Evelin Alves; RIBEIRO, Vanessa; SANTOS, Maria Aparecida do Nascimento dos; GUIMARÃES JÚNNYOR, Wellingthon da Silva; RIBEIRO, Genicelli Mafra (ANAIS DO ENIC, 2024)
-